Imágenes e imaginarios sobre España en México : siglos XIX y XX / coordinadores Agustín Sánchez Andrés, Tomás Pérez Viejo, Marco Antonio Landavazo - Sánchez Andrés, AgustínPérez Vejo, TomásLandavazo Arias, Marco Antonio
Bibliografía por capítulos